2021
DOI: 10.3892/etm.2021.10767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psoralea corylifolia L. seed extract on AGEs‑induced cell proliferation and fibrotic factor expression in mesangial cells

Abstract: Diabetic nephropathy is a microvascular complication of diabetes that is characterized by mesangial expansion and thickening of the glomerular basement membrane. The production of advanced glycation end products (AGEs) increases in diabetic patients. Activation of the receptor of AGE (RAGE) signaling pathway induces mesangial expansion via the reactive oxygen species (ROS)-mediated production of pro-inflammatory and extracellular matrix molecules. The Psoralea corylifolia L. seed (PCS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Supplementary to these previous findings, the current study further showed that AGEs upregulated the expression of K17 and resulted in the nuclear export and degradation of p27 KIP1 , leading to progressed cell cycle and ultimately the proliferation of keratinocytes. Multiple studies have demonstrated the pro-proliferative effects of AGEs on different types of cells like mesangial cells and aortic smooth muscle cells [25][26][27]. However, some other studies have claimed the inhibitory effects of AGEs on cell proliferation or cell cycle progression in ovarian granulosa cells and intestinal epithelial cells [58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary to these previous findings, the current study further showed that AGEs upregulated the expression of K17 and resulted in the nuclear export and degradation of p27 KIP1 , leading to progressed cell cycle and ultimately the proliferation of keratinocytes. Multiple studies have demonstrated the pro-proliferative effects of AGEs on different types of cells like mesangial cells and aortic smooth muscle cells [25][26][27]. However, some other studies have claimed the inhibitory effects of AGEs on cell proliferation or cell cycle progression in ovarian granulosa cells and intestinal epithelial cells [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Given that AGEs are able to induce the proliferation of various types of cells [19,[25][26][27], we speculated that increased AGEs could contribute to the excessive proliferation of epidermal keratinocytes in psoriasis. To verify this, we first examined the growth of NHKs treated with BSA-AGEs via CCK8 assay and resazurin-reduction assay.…”
Section: Ages Promote the Proliferation Of Keratinocytes Via Upregula...mentioning
confidence: 99%
“…[ 40,41 ] Eclipta prostrata leaf extract mediated CuONPs synthesized and screened for its antimicrobial activity. [ 42 ] In this work, to study the antimicrobial activity of CuONPs, we used Prunella vulgaris (P. Vulgaris) , a perennial herbaceous plant of the labiaceae family. P. vulgaris , commonly known as self‐heal, has been used as a traditional medicinal plant in various parts of the world such as Asia, Europe, and North America.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic hyperglycemia, highly reactive metabolites produced during glycolysis are the main cause of impaired normal cell function, resulting in different types of chronic diseases [20]. Among them, methylglyoxal (MGO) is the most reactive dicarbonyl substance, it usually binds to the amino acids, especially, arginine and lysine, to form advanced glycation end-products (CEL, MGH1, etc) which ultimately deteriorate normal protein functions [21]. MGO has been reported to play a critical role in different central nervous system (CNS) cognitive functions, particularly anxiety, stress, depression, and neurodegenerative diseases [22].…”
Section: Introductionmentioning
confidence: 99%